2002
DOI: 10.1017/s1047951102000264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an intravenous pulse of methylprednisolone versus oral corticosteroid in severe acute rheumatic carditis: a randomized clinical trial

Abstract: Intravenous treatment of methylprednisolone, as a single anti-inflammatory agent, was inferior to conventional treatment with oral prednisone in the control of severe rheumatic carditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…In a small study comparing intravenous steroid with oral corticosteroids in Brazil, there appears to be better treatment outcomes with the oral regimen. 18 On the other hand, a study by Torres et al found that combining pulse methylprednisolone and oral prednisolone appear to contribute to both reduced left chamber dimensions and prevention of rebound phenomenon. 19 A meta-analysis of the treatment of Group A streptococcus pharyngitis to prevent acute rheumatic fever concluded that there would be an approximately 60% reduction in cases of acute rheumatic fever if pharyngitis was appropriately treated, especially in endemic areas.…”
Section: Discussionmentioning
confidence: 98%
“…In a small study comparing intravenous steroid with oral corticosteroids in Brazil, there appears to be better treatment outcomes with the oral regimen. 18 On the other hand, a study by Torres et al found that combining pulse methylprednisolone and oral prednisolone appear to contribute to both reduced left chamber dimensions and prevention of rebound phenomenon. 19 A meta-analysis of the treatment of Group A streptococcus pharyngitis to prevent acute rheumatic fever concluded that there would be an approximately 60% reduction in cases of acute rheumatic fever if pharyngitis was appropriately treated, especially in endemic areas.…”
Section: Discussionmentioning
confidence: 98%
“…Trials of corticosteroids or related compounds (adrenocorticotrophic hormone) have been unconvincing, including a comparative study of methylprednisolone and oral prednisolone in 18 patients. 30 Meta-analyses have also failed to show benefit. 31 Despite this, the national guideline observes that 'corticosteroids are sometimes used for severe carditis, although there is no evidence that they alter the longer-term outcome'.…”
Section: Disease-modifying Treatmentsmentioning
confidence: 99%